The mediating role of the big five personality traits in the relationship between self-efficacy and depressive symptoms among Chinese university students - Yang, Yu; Mou, Zhen; Zhang, Lingling; Ma, Shurong; Zhao, Zhenxiong (Frontiers in Psychiatry, 2025)
BackgroundThe mental health of university students, particularly depression, has become a significant public health concern in China. While previous studies have highlighted the link between self-efficacy and mental health, especially concerning depressive symptoms, the potential mediating role of the big five personality traits in this relationship remains underexplored. This study aims to examine the relationships among self-efficacy, the big five personality traits, and depressive symptoms through a mediation model.MethodsThis cross-sectional study utilized a multi-stage stratified random sampling method to survey residents across 23 provinces in China, ultimately enrolling 1,193 university students aged 19-25. Measures included the PHQ-9 to assess depressive symptoms, the BFI-10 to evaluate personality traits, and the NGSES for self-efficacy. Hierarchical regression, random forest regression, mediation analyses, and restricted cubic spline (RCS) models were conducted using R software.ResultsThe prevalence of depressive symptoms among university students was 21.8%. Neuroticism (p<0.001) was a positive predictor of depressive symptoms, while agreeableness (P<0.001) and conscientiousness (P<0.001) were negative predictors. And agreeableness [Effect = -0.028, 95% CI (-0.045, -0.014)], conscientiousness [Effect = -0.043, 95% CI (-0.067, -0.023)], and neuroticism [Effect = -0.048, 95% CI (-0.070, -0.029)] significantly mediated the relationship between self-efficacy and depressive symptoms. Additionally, a potential nonlinear relationship (p for nonlinearity < 0.001) was identified between self-efficacy and depressive symptoms.ConclusionsSelf-efficacy shows a direct positive association with depressive symptoms when controlling for personality traits, with neuroticism, agreeableness, and conscientiousness serving as key mediators. This highlights that the effect of self-efficacy on depression depends critically on personality, emphasizing the need to consider these traits in interventions for university students’ mental health.